2022
DOI: 10.1186/s12905-022-01729-7
|View full text |Cite|
|
Sign up to set email alerts
|

Association between resting-state EEG oscillation and psychometric properties in perimenopausal women

Abstract: Background The perimenopausal period is associated with a higher risk of various mood disorders. Similarly, although resting-state electroencephalogram (rsEEG) brain oscillatory activity has been associated with various neuropsychological disorders and behaviours, these issues have not been assessed in perimenopausal women. This study aimed to evaluate quantitative relationships between psychometric properties and rsEEG rhythms (delta, theta, alpha, beta and gamma powers) in perimenopausal wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…58 Previous studies using EEG have reported that patients with sleep difficulties during the menopausal transition showed increased beta oscillatory intensity during sleep, 66 and impulsivity associated with menopause was positively related to the beta power. 67 These findings also support our observation that participants with more severe unpleasantness showed enhanced beta oscillatory activity. In contrast, gamma oscillatory activity has a much higher frequency and is associated with neural inhibition 68 (ie, gain control) in cortices and provides insights into activity in local cortical networks.…”
Section: Brain Activity and Menopausal Symptomssupporting
confidence: 88%
See 1 more Smart Citation
“…58 Previous studies using EEG have reported that patients with sleep difficulties during the menopausal transition showed increased beta oscillatory intensity during sleep, 66 and impulsivity associated with menopause was positively related to the beta power. 67 These findings also support our observation that participants with more severe unpleasantness showed enhanced beta oscillatory activity. In contrast, gamma oscillatory activity has a much higher frequency and is associated with neural inhibition 68 (ie, gain control) in cortices and provides insights into activity in local cortical networks.…”
Section: Brain Activity and Menopausal Symptomssupporting
confidence: 88%
“…All sensory inputs to the cortices, except for olfactory, are relayed by the thalamus, which is rich in sex hormone receptors 56,57 and plays an important role in sensory gain control 58 . Previous studies using EEG have reported that patients with sleep difficulties during the menopausal transition showed increased beta oscillatory intensity during sleep, 66 and impulsivity associated with menopause was positively related to the beta power 67 . These findings also support our observation that participants with more severe unpleasantness showed enhanced beta oscillatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 45 studies were identified that met the inclusion criteria for this scoping review. Twenty-five studies utilized EEG frequency waves as outcome measures (e.g., Delta, Theta, Alpha, Beta, Gamma), while 19 studies employed ERP as outcome measures (e.g., P3, P2, N1, N2, P1, N170), and one study (Wong et al, 2018) (Benoit et al, 2021;Bi et al, 2022;Cai et al, 2022;Campbell-Yeo et al, 2022;Cao et al, 2015;Cao et al, 2017; Francisco et al, 2019;Gong et al, 2022;Hwang et al, 2019;Hwang et al, 2022;Kim et al, 2018;Kim et al, 2022;Lees et al, 2020;Peters et al, 2014;Shepherd et al, 1999;Shiroshita et al, 2021;Sung et al, 2022;Välimäki et al, 2021;Yang et al, 2012;Yang et al, 2016;Zhao et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in this review involved 14 countries, mainly including 12 studies from China, six from Korea, five from the United States, five from Australia, and four from Japan. There were 26 studies conducted in cooperation with researchers in nursing and other disciplines, especially with psychology and neuroscience researchers (Benoit et al, 2021; Bi et al, 2022; Cai et al, 2022; Campbell‐Yeo et al, 2022; Cao et al, 2015; Cao et al, 2017; Cao, Si, Li, & Guo, 2022; Cao, Si, Li, Guo, & Yue, 2022; Cui et al, 2021; Dai et al, 2016; Fitriana et al, 2021; Francisco et al, 2019; Gong et al, 2022; Hwang et al, 2019; Hwang et al, 2022; Kim et al, 2018; Kim et al, 2022; Lees et al, 2020; Peters et al, 2014; Shepherd et al, 1999; Shiroshita et al, 2021; Sung et al, 2022; Välimäki et al, 2021; Yang et al, 2012; Yang et al, 2016; Zhao et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation